Soil erosion estimation using USLE/RUSLE in Kaski district (OODBODHAN, 2025)
Soil erosion is a major environmental concern in Nepal’s mid-hill regions, particularly in areas like Kaski District where steep slopes, intense rainfall, and changing land use contribute to land degradation. This study aims to assess soil erosion loss in Kaski District by applying the Universal Soil Loss Equation (USLE) and the Revised Universal Soil Loss Equation (RUSLE) models. Utilizing available datasets such as SRTM DEM for slope and aspects data, CHIRPS rainfall data, NARC soil data and ICIMOD land use landcover map, soil erosion loss maps were generated to identify soil erosion patterns. The results show that both USLE and RUSLE models effectively captured the spatial variability of soil erosion across the district, with USLE producing slightly higher estimates than RUSLE. Erosion rates were found to be lower in the southern parts of the district and increased progressively toward the northern mountainous regions. The model outputs were consistent with findings from previous studies in Kaski and similar terrain, supporting the validity of these models for erosion prediction in Kaski. The study highlights the usefulness of USLE and RUSLE as practical tools for soil loss estimation and provides a foundation for future research, land management planning, and soil conservation initiatives in the region.